Sistem Informasi Keputusan Menentukan Menu Makanan Bagi Penderita Diabetes Menggunakan Metode Fuzzy Analytic Hierarchy Process - helmina, helmina; Akbar, Zulfikri; Dani, Rian (Institut Agama Islam Negeri (IAIN) Curup, 2022)
A fresh meal menu for diabetes patients is something significant to help them control their blood sugar levels. Diabetes is one of the diseases that cannot be cured quickly according to several studies. One of the methods to treat diabetes is by controlling the food consumed by patients. With good eating habits, the progress of diabetes can be slowed down. The food consumed by diabetes patients must be adjusted according to the number of calories, meal schedules, and the type of food based on the patient's condition. The input of the developed application consists of guidelines, sub-criteria, and replacement information, while the output is in the form of suggested information from the obtained decision. The system is developed using Borland Delphi 7 programming language and Microsoft Access 2007 database. The system provides suggestions in the form of information resulting from the calculation using the Fuzzy Analytic Hierarchy Process method. The decision support system ensures that the meal menu for diabetes patients is prioritized to provide fresh meal options for them.